Bioavailability of soil organic matter and microbial community dynamics upon permafrost thaw - Coolen, Marco; van de Giessen, J.; Zhu, E.; Wuchter, C. (2011)
Amplified Arctic warming could thaw 25% of the permafrost area by 2100, exposing vast amounts of currently fixed organic carbon to microbially mediated decomposition and release of greenhouse gasses through soil organic matter (SOM) respiration. We performed time-series incubation experiments with Holocene permafrost soils at 4°C for up to 11 days to determine changes in exoenzyme activities (EEAs) (i.e. phosphatase, β-glucosidase, aminopeptidase) as a measure for the bioavailability of SOM in response to permafrost thaw. We also profiled SSU rRNA transcripts to follow the qualitative and quantitative changes in viable prokaryotes and eukaryotes during incubation. EEA, amount of rRNA transcripts and microbial community structures differed substantially between the various soil intervals in response to thaw: after 11 days of incubation, the active layer became slightly depleted in C and P and harboured bacterial phyla indicative of more oligotrophic conditions (Acidobacteria).A fast response in phosphatase and β-glucosidase upon thaw, and a predominance of active copiotrophic Bacteroidetes, showed that the upper permafrost plate serves as storage of easily degradable carbon derived from the overlying thawed active layer during summer. EEA profiles and microbial community dynamics furthermore suggest that the deeper and older permafrost intervals mainly contain recalcitrant SOM, and that extracellular soil-bound exoenzymes play a role in the initial cleavage of biopolymers, which could kick-start microbial growth upon thaw. Basidiomycetous fungi and Candidate Subdivision OP5 bacteria were the first to respond in freshly thawed deeper permafrost intervals, and might play an important role in the decomposition of recalcitrant SOM to release more labile substrates to support the major bacterial phyla (β-Proteobacteria, Actinobacteria, Firmicutes), which predominated thereafter.